Investimentos dos governos subnacionais no Brasil: Estimaç\~ao e análise por modelos de expaço de estado - Rodrigo Octávio Orair; Wesley de Jesus Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– There are many problems involved in estimating high frequency series for subnational governments. Space State Model (SSM) is a framework capable of handling some of these problems. The techniques that emerge from this approach (temporal disaggregation and nowcasting) are used to estimate monthly series for capital investments by subnational governments in Brazil during 2002-2011. SSM are also used to analyze the dynamic properties of time series. One of the most interesting results is the newly evidence of electoral cycles on investments of both municipalities and states in Brazil. These techniques might be easily generalized for other relevant series. The main objective of this work is to present a methodological framework for estimating and analyzing the development of high frequency series for Brazilians subnational governments. It offers a useful instrument for monitoring fiscal policy and for applied macroeconomic research.
Keywords: C82; E69; H72; 330; public investment; space state model; subnational public finance